Waste, weeds, and wild food - Flaminia Paddeu (EchoGéo)
The aim of this paper is to define the scope and an initial agenda for a critical geography of urban food collecting. It provides an overview of a multidisciplinary literature regarding patterns of foraging and scavenging to develop a theoretical comprehension of urban collecting in contemporary northern cities. Drawing on three bodies of critical geography literature, namely urban informality studies, radical food studies, and urban political economy and ecology, it advocates that investigating urban food collecting provides a tool to analyze structural forms of power, exclusion, injustice and inequality as well as alternative pathways in spaces of advanced capitalism.